Migration, diversity and regional risk sharing. Issue 44 (20th September 2021) - Ventura, Luigi; Ventura, Maria
ABSTRACT: The economic consequences of migration have become the topic of many recent contributions in theoretical and applied economics. However, only a handful of papers have dealt with the implications of migration for risk sharing. We intend to fill in this gap in the literature by exploring the effects of migration and the ensuing cultural diversity on risk sharing in receiving economies, by using data on US states in the period 2000–2015. Our empirical results strongly suggest that migration enhances risk sharing in host economies, but non monotonically so. Moreover, cultural diversity is key in this risk sharing-enhancing effect of migration.